(untitled) (The Pakistan Development Review, 2000)
It follows from the experience of World economies that rising and balanced use of fertilisers is the key factor in agricultural productivity [FAO (1995); SFS and STI (1996); Habib-ur-Rehman (1982) and Pinstrup-Anderson (1976)]. In the case of Pakistan the stepped up fertiliser use has been argued to be incritable to realise existing untapped yield potential of major crops [Johnston and Kilby (1975)] and to induce yield increasing technological change in future [John Mellor Associates and Asianics Agro-Dev. International (1993)]. Although proper malnutrition involves the use of primary, secondary and micro-nutrients, Nitrogen (N), Phosphorus and Potassium (K) or NPK is generally considered to be sufficient to harvest normal crop yields [FAO and IFA (1999)]. Given this situation, this paper looks at various factors that determine fertiliser use in Pakistan. Although price of fertiliser is a critical factor in this respect [Schultz (1965) and Johnston and Cownie (1969)], only non-price factors are considered in this paper due to limitations of data. Apart from this introductory section, the paper comprises of three more sections. The following Section 2 explains the data and the empirical model. Section 3 presents the results. Section 4 summarises the main findings along with their policy implications.